Evaluation of Radionuclides Transfer Factors and Ingestion Dose from Plants Around Mining Sites in Adamawa State Nigeria (International Journal of Natural Sciences Research, 2022)
Illegal mining activities has become rampant in Adamawa State Nigeria, contaminating the soil with radionuclides which can be transferred to the food crops farmed in the host communities. Ingestion of such plants could cause harmful effects. In this study, radionuclide transfer factor from soil to plants and internal exposure dose around mining sites in Adamawa State were evaluated. 30 (15 soil, 15 plant) samples were analyzed for activity concentrations of 226Ra, 232Th and 40K. The transfer factor from soil to plant was calculated and the ingestion dose was also calculated using the Integrated Module for Bioassay Analysis (IMBA). Result shows that the mean activity concentrations of 226Ra, 232Th and 40K in the soil are 106.32Bq/kg, 84.34Bq/kg and 466.14Bq/kg, while for plants are 98.42Bq/kg, 72.69Bq/kg and 274.07Bq/kg respectively. These values were above the world average by United Nations Scientific Community on the Effects of Atomic Radiation (UNSCEAR) 35Bq/kg, 30Bq/kg and 400Bq/kg except for 40K which was lower in plant samples. Mean transfer factors were 0.942, 0.919 and 1.149 respectively, corresponding to a mean ingestion dose of 1.02E-01mSv/y, indicating high transfer factor in all the mining sites and high ingestion doses. Even though the mean ingestion dose was low, ingestion of such plants may pose radiation risk to the host communities in a long time. Therefore, proper policy by regulatory authorities must be put in place to protect the host community and the public from high ingestion doses that accounts for internal radiation exposure especially mining sites A, B and C.